STRATEGI KOMUNIKASI KIAI DESADALAM UPAYA PEMBERDAYAAN REMAJA DEMAM TOGEL : (STUDI ATAS DESA BENDUSA KECAMATAN ARJASA SITUBONDO) - Karim, Syafii (STIT Al - Ibrohimy Bangkalan, 2019)
After reading this article, we will find out about the Communication Strategy of Kiai Desa Bandusa in dealing with teenagers who are again lottery fever. The academic interest in this paper is in the realm of the Kiai Desa Bandusa approach in an effort to empower Togel fever youth who are not only hard Power approaches, namely militaristic nuances of violence which will only give birth to new forms of crime from the positive impact of lottery gambling. If we observe from the symptoms raised by the youth of the lottery fever, there are several variants of deviant actions, starting with them coming to the sacred places, coming to the shadows to make noise in their village. So from this, the steps taken by the Bandusa village clerics by using Soft Power appraisal were by gentle approaches to the young people of Togel fever. The basic questions of this study are 1). What is the communication planning strategy of Kiai Desa Bandusa in the empowerment of teenagers with lottery fever? 2). How is the communication action strategy of Kiai Desa Bandusa in the empowerment of young people with lottery fever ?. To answer this question in depth the author uses a qualitative descriptive method with a phenomenological approach. In this paper a communication planning strategy was found that began with the process of thinking or planning strategic steps which then took the form of short, medium and long term planning. Furthermore, the action strategy carried out by Kiai Bandusa Village is manifested in several constructs of activities. The first is to coordinate with government agencies at the lowest level starting from the household, rw, village head, Kepolisin to the Bupati. Second, have a dialogue with the youth of lottery fever. Third, giving some skills to young people with lottery fever by presenting several presenters who are truly competent in their field.